Blurred Lines Between Determinism and Stochasticity in an Amphibian Phylosymbiosis Under Pathogen Infection - Longo, Ana V.; Solano‐Iguaran, Jaiber J.; Valenzuela‐Sánchez, Andrés; Alvarado‐Rybak, Mario; Azat, Claudio; Bacigalupe, Leonardo D. (Molecular ecology, 2025)
ABSTRACT Selection, dispersal and drift jointly contribute to generating variation in microbial composition within and between hosts, habitats and ecosystems. However, we have limited examples of how these processes interact as hosts and their microbes turn over across latitudinal gradients of biodiversity and climate. To bridge this gap, we assembled an extensive dataset of 580 skin bacteriomes from 22 amphibian species distributed across a 10° latitudinal range in Chile. Amphibians are susceptible to the fungal pathogen Batrachochytrium dendrobatidis (Bd), which infects their skin, potentially leading to changes in the normal skin microbiome (i.e., dysbiosis). Using comparative methods, accounting for pathogen infection and implementing resampling schemes, we found evidence of phylosymbiosis, characterised by more similar bacterial communities in closely related amphibian species. We also compared how neutral processes affected the assembly of skin bacteria by focusing on two widespread species from our dataset: the Chilean four‐eyed frog (Pleurodema thaul) and Darwin's frog (Rhinoderma darwinii). Neutral models revealed that dispersal and chance largely facilitated the occurrence of ~90% of skin bacteria in both species. Deterministic processes (e.g., phylosymbiosis, active recruitment of microbes, microbe–microbe interactions) explained the remaining fraction of the bacteriomes. Amphibian species accounted for 21%–32% of the variance found in non‐neutral bacterial taxa, whereas the interaction with Bd carried a weaker but still significant effect. Our findings provide evidence from ectotherms that most of their skin bacteria are subject to dispersal and chance, yet contemporary and historical contingencies leave strong signatures in their microbiomes even at large geographical scales.